Pengaruh Pendaptan Asli Daerah dan Dana Bagi Hasil Terhadap Pertumbuhan Ekonomi melalui Belanja Langsung di Provinsi Bali - Dewi, Ni Wayan Nuryanti; Sri Budhi, I Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
This study aims to review the effectiveness of regional autonomy in maximizing economic growth, as well as examine how the influence of local revenues and revenue-sharing fund on economic growth through direct expenditure in the District / City of Bali Province. The samples using purposive sampling technique, with the criteria in the realization of the budget has been classified direct and indirect expenditure clearly. Namely 7-year observation period, consisting of 2007-2013. Methods of data analysis done by path analysis and Sobel test. The results obtained showed regional revenue directly influence the Direct Expenditure and Revenue Sharing Fund does not directly influence the Direct Expenditure. Furthermore, DBH and Direct Expenditure directly affect economic growth, while local revenue does not directly affect economic growth. Then the local revenue indirect effect on economic growth through direct expenditure, while DBH no indirect effect on the economic growth through direct expenditure.
Keywords: Local revenue; Revenue sharing fund; Direct expenditure; Economic growth